Visual characteristics as a key factor in species selection in vegetation planes design - Marko DOBRILOVIČ; Ana KUČAN; Nika KRAVANJA (Acta Agriculturae Slovenica)
In the past, the selection of plants used to rest upon individual taste and fashion dictates of the period, rather than starting from and following directives determined by the goal of creating a certain space characteristics. In the literature the plant species are frequently treated individually and arranged according to the visual effect of each plant. In order for this research to satisfy the needs of design practice, it was necessary to ascertain the hidden designer potential of each plant, which is not identical with the pleasing effect of the plant. This is how the central problem is formulated in this research: to determine the selection criteria (of plant species), arising from the visual characteristics of the plants and, based on these criteria to determine the suitability of plants in order to create visual effects of vegetation planes. In this sense we can expose the importance of proving the connectedness between morphological properties of the plants and the characteristics of vegetation planes, which are formed by these very plants. The subject of this research is plant material, 208 shrubs and 193 trees, systematized according to their size, shape, habitus, texture, colour, as well as the seasonal appearance of individual characteristics. We established the method and criteria for the selection of morphological properties of the plants that allow us to achieve a certain visual character of the vegetational plane. The process of plants selection is shown on concrete examples, whereby certain design demands determine the choice of the adequate plants. For the final selection of plants it is necessary to add criteria arising from eco-physiological needs of the plants and from technological demands.